Analysis of Absorbable Hemostatic Packing Compared to Physiologic Hemostasis in Functional Endoscopic Sinus Surgery With or Without Septoplasty. Issue 5 (September 2019) - Comer, Brett T.; Alfonso, Kristan P.; Doyle, Edward J.; Gallogly, James A.; Simpson, Matthew C.; Antisdel, Jastin L.
Background: There currently are no randomized studies examining if absorbable hemostatic packing (AHP) results in better objective and subjective outcomes than physiologic healing in sinus surgery with or without septoplasty. Objective: The objective of this study is to examine outcomes after functional endoscopic sinus surgery (FESS) with or without septoplasty with the use of AHP versus physiologic hemostasis and healing. Methods: A prospective randomized control trial was performed at 2 tertiary academic institutions. Fifty-nine patients undergoing bilateral FESS with or without septoplasty were enrolled and randomized to receive AHP in 1 middle meatus and no packing contralaterally. Subjective outcomes (pain, bleeding, obstruction, discharge) on self-reported visual analog scale questionnaires were tabulated on postoperative days 0, 1, 7, and 14 by the patient. Endoscopic outcomes (synechiae formation, edema, infection, granulation, debridement, crusting) were measured at 1 week, 2 weeks, and 6 weeks postoperatively by their surgeon. Results: No significant differences were identified in subjective or endoscopic outcomes with AHP use. Concurrent septoplasty patients with AHP experienced no sustainable difference in subjective or endoscopic outcomes compared to septoplasty control. No sustainable differences were found among the types of AHP or the 2 surgeons. Conclusion: This first reported prospective randomized study of patients with nonstrict selection criteria found AHP made no significant difference on subjective and objective postoperative outcomes as compared to physiologic hemostasis. Previous AHP-specific studies have shown differences in carefully selected patient groups. Generalizing study-proved benefits of specific AHP to all AHP is shown to be not appropriate.